Increased proteolytic cleavage of osteoglycin is associated with a stable plaque phenotype and lower risk of cardiovascular events. (August 2022) - Al-Sharify, Dania; Nielsen, Signe Holm; Matthes, Frank; Tengryd, Christoffer; Sun, Jiangming; Genovese, Federica; Karsdal, Morten A.; Nilsson, Jan; Goncalves, Isabel; Edsfeldt, Andreas
Abstract: Background and aims: Extracellular matrix (ECM) remodeling is one of the key components in the formation of vulnerable atherosclerotic plaques and cardiovascular events. We recently showed that the full-length ECM-proteoglycan osteoglycin was associated with plaque vulnerability and future cardiovascular events. In the present study, we aimed to investigate the association of cleaved osteoglycin with plaque phenotype. Methods: Two-hundred human carotid plaques were analyzed by immunohistochemistry. Cleaved osteoglycin and active caspase-3 were assessed by ELISA. ECM components (collagen, elastin and glycosaminoglycans) were assessed by colorimetric assays in plaque tissue homogenates. Matrix metalloproteinases (MMPs) were assessed using Milliplex. MMP-cleavage of osteoglycin and its effect on apoptosis were studied in vitro . Cardiovascular events were recorded during follow-up using national registries. Results: Plaque levels of cleaved osteoglycin were significantly higher in asymptomatic plaques and correlated to α-actin plaque area, collagen, elastin and inversely to lipids, active. caspase-3 and a histological vulnerability index. Cleaved osteoglycin correlated to several MMPs, especially MMP-12, which was also shown to cleave osteoglycin in vitro . In vitro cleavage of osteoglycin was also associated with less smooth muscle cell apoptosis. Patients with high plaque levels of cleaved osteoglycin had a significantly lower risk to suffer from future cardiovascular events. Conclusions: The current study shows that cleaved osteoglycin is associated with a stable plaque phenotype and lower risk for future cardiovascular events. Potentially due to reduced cell apoptosis and ability to retain LDL. These results indicate that targeting the cleavage of osteoglycin may be a potential therapeutic strategy to stabilize plaques. Graphical abstract: Image 1 Highlights: Plaque levels of cleaved osteoglycin are higher in plaques from asymptomatic patients and patients without diabetes. High plaque levels of cleaved osteoglycin are associated with a stable plaque phenotype and a lower risk for cardiovascular events. The cleavage process of osteoglycin may be a potential therapeutic target for the stabilization of vulnerable plaques.